2018
DOI: 10.7150/thno.26643
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic precursors differentiated from human blood-derived induced neural stem cells improve symptoms of a mouse Parkinson's disease model

Abstract: Autologous neural stem cells (NSCs) may offer a promising source for deriving dopaminergic (DA) cells for treatment of Parkinson's disease (PD).Methods: By using Sendai virus, human peripheral blood mononuclear cells (PBMNCs) were reprogrammed to induced NSCs (iNSCs), which were then differentiated to dopaminergic neurons in vitro. Whole-genome deep sequencing was performed to search for mutations that had accumulated during the reprogramming and expansion processes. To find the optimal differentiation stage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…The use of an episomal vector is inexpensive and easily adaptable for reprogramming a variety of cell types, including iPSCs and iNSCs. Episomal vectors are eliminated from these iPSCs via several passages through cell divisions, which can take several months to achieve transgene-free iPSCs ( 30 , 32 ). However, Xu and colleagues indicated that piNPCs contained virtually undetectable amounts of EBNA-1, but episomal vector-transfected PFFs carried approximately 100 copies per cell, suggesting that EBNA-1 was not present in the piNPC genome ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of an episomal vector is inexpensive and easily adaptable for reprogramming a variety of cell types, including iPSCs and iNSCs. Episomal vectors are eliminated from these iPSCs via several passages through cell divisions, which can take several months to achieve transgene-free iPSCs ( 30 , 32 ). However, Xu and colleagues indicated that piNPCs contained virtually undetectable amounts of EBNA-1, but episomal vector-transfected PFFs carried approximately 100 copies per cell, suggesting that EBNA-1 was not present in the piNPC genome ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…These methods may result in insertional mutagenesis and the persistence or reactivation of transgenes. Moreover, therapeutic translation of this technique will require a thorough safety evaluation of mutations that occurred during the reprogramming process, as well as a fast derivation and differentiation strategy ( 32 ). A Sendai virus (SeV) vector can overcome these issues due to its single-stranded RNA virus propagating in the cytoplasm of infected cells that neither pass through a DNA phase nor integrate into the host genome, unlike other viruses.…”
Section: Introductionmentioning
confidence: 99%
“…The use of episomal vector is very inexpensive and easily adaptable to reprogramming a variety of cell types, both iPSCs and iNSCs. Episomal vectors are eliminated from these iPSCs by several passages through cell divisions, which can take several months to achieve transgene-free iPSCs [30,42]. However, Xu and colleagues indicated that ipNPCs contained virtually undetectable amounts of EBNA-1, but episomal vector-transfected PFFs carried approximately 100 copies per cell, suggesting that EBNA-1 was not present in the ipNPC genome [27].…”
Section: Discussionmentioning
confidence: 99%
“…These methods may result in insertional mutagenesis and the persistence or reactivation of transgenes. Moreover, therapeutic translation of this technique will require a thorough safety evaluation of any mutations gained during the reprogramming process, as well as a fast derivation and differentiation strategy [30]. A Sendai virus (SeV) vector can overcome these issues owing to a single-stranded RNA virus propagating in the cytoplasm of infected cells that does neither pass a DNA phase nor integrate into the host genome, unlike the other viruses.…”
Section: Introductionmentioning
confidence: 99%
“…iNSCs were generated from reprogrammed human blood mononuclear cells following our previous method and transfected EGFP. The iNSCs was identitied by NSC markers Sox1, Sox2, OLIG2, PAX6, NESTIN, GFAP and Ki67 (9). Subsequently, iNSCs were seeded in 0.6%, 0.8%, 1.0%, 1.2%, and 1.8% HA hydrogels in 48-well plates at the concentration of 2×10 5 cells per well.…”
Section: Culture Of Inscsmentioning
confidence: 99%